Comparison of Pre- and Posttreatment Airway Volume in Patients with Temporomandibular Joint Disorders Treated with Ultra-Low Frequency Transcutaneous Electrical Nerve Stimulation Using Cone Beam Computed Tomography - Verghese, Rhea Susan; Jose, Renju; Ramachandran, Anu; Shanmugham, Aravind M.; Nair, Priya K.; Kumar, Krishna S.; Varma, Beena R. (International Archives of Otorhinolaryngology, 2023)
Introduction Temporomandibular joint disorders (TMD) present with a multitude of symptoms that can range from headaches to shoulder pain. Patients frequently present with pain in the ear, dizziness, and vertigo. It is noted that some patients who report TMDs also have a history of sleep disturbances, which is noted in cone beam computed tomography (CBCT) as a reduction in the oropharyngeal airway volume.Objective To evaluate the airway volume in pre- and posttreatment of TMD with the use of neuromuscular orthotics made with ultra-low frequency transcutaneous electrical nerve stimulation (ULF-TENS).Methods A total of 15 patients were evaluated for TMDs using the related criteria. Those included were treated with ULF-TENS with evaluation of the airway volume both pre- and posttreatment using CBCT and the Dolphin 3D volume analysis software.Results While the symptoms were shown to be significantly reduced in patients who were treated with this particular modality, the airway volume varied in those who reported a reduction after a period of 3 months and those that reported after a period of 6 months.Conclusion Posttreatment evaluation of the airway should be done after a period of 6 months for a more objective evaluation. A multidisciplinary evaluation of the patient is required in such cases.
Keywords: transcutaneous electrical nerve stimulation; temporomandibular joint disorders; cone beam computed tomography; oropharyngeal airway volume